The Influence of Speed of Service Time, Officer Competence, Facilities and Infrastructure on Service Quality and Its Impact on Customer Satisfaction(Study on Services at the Jambi Provincial Health Laboratory Center) - Ferdiyan, Rendra; Yuliaty, Farida; Rulia (Journal of Jabar Economic Society Networking Forum, 2024)
This study aimed to analyze the direct and indirect effects of the speed of service time, the competence of officers, and facilities and infrastructure on customer satisfaction which was mediated by service quality. The research was conducted at the Technical Services Unit of Jambi Provincial Health Laboratory Center. The populations in this study were customers who used services at the Technical Services Unit of Jambi Provincial Health Laboratory Center. The sample in this study was selected using the accidental sampling method, which were service users of Technical Services Unit of Jambi Provincial Health Laboratory Center whom were met by researchers randomly. In this research, data analysis used the Partial Least Square (PLS) approach. The research results showed that: speed of service time, and facilities and infrastructure had a direct influence on service quality and customer satisfaction, while officer competency had a direct influence on service quality but has no direct influence on customer satisfaction. Meanwhile, speed of service time and officer competency had indirect influence on customer satisfaction which was mediated by service quality, while facilities and infrastructure did not have indirect influence on customer satisfaction which was mediated by service quality.